The Effect of Corporate Characteristics on Capital Structure in Indonesia - Nicko Albart; Bonar Marulitua Sinaga; Perdana Wahyu Santosa; Trias Andati (Universitas Hayam Wuruk Perbanas, 2020)
This study aims to determine the effect of corporate characteristics on the company's capital structure, which plays a fundamental role in the proportion of debt and equity financing risks. The research method used is purposive sampling. This research's population is non-financial issuers listed on the Indonesia Stock Exchange with quarterly data for the period of 2010-2017. The analysis is performed using panel data with six independent variables and two control variables. The results of this study indicate that profitability and institutional ownership have a negative effect on capital structure. In contrast, market ratios, firm size, and managerial ownership have a positive effect on capital structure. Debt decision making must consider financial and ownership characteristics, especially if there is institutional or government ownership in the company because company characteristics have a significant effect on the company's capital structure.